2014
DOI: 10.2147/clep.s53706
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported knowledge and awareness about blood pressure and hypertension: a cross-sectional study of a random sample of men and women aged 60–74 years

Abstract: BackgroundIn general, it is assumed that patient education, by increasing knowledge, may change behavior and lifestyle and promote health. In this context, it is a surprise that knowledge and awareness about blood pressure and hypertension among elderly people is poor. We hypothesized that knowledge about blood pressure and hypertension would be better among individuals with self-reported hypertension compared with subjects without self-reported hypertension.MethodsWe mailed a questionnaire to a random sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Participants might perceive the threat of hypertension as low. Indeed, several studies have reported that, for the public, hypertension does not seem to pose a threat . Steiner and coworkers suggested that the majority of the public does not know that hypertension is mostly an asymptomatic disease known as “the silent killer.” According to a study by Petrella and Campbell, most of the general public in Canada is unaware of the association between hypertension and heart disease and believes that hypertension is not a serious medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Participants might perceive the threat of hypertension as low. Indeed, several studies have reported that, for the public, hypertension does not seem to pose a threat . Steiner and coworkers suggested that the majority of the public does not know that hypertension is mostly an asymptomatic disease known as “the silent killer.” According to a study by Petrella and Campbell, most of the general public in Canada is unaware of the association between hypertension and heart disease and believes that hypertension is not a serious medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…HTN is often associated with not having symptoms or reported as unrecognizable symptoms. We found five quantitative studies in this review that discussed HTN as asymptomatic [34,53,54,63,64] or having symptoms that may be periodically present [49]. Most of these studies associated knowledge or lifestyle behavior with beliefs surrounding HTN.…”
Section: Absence Of Symptomsmentioning
confidence: 99%
“…Most of these studies associated knowledge or lifestyle behavior with beliefs surrounding HTN. Several studies attributed participants reporting 'no symptoms' as a lack of knowledge [34,54,57]. However, cultural factors were influential in three of the studies [34,53,63].…”
Section: Absence Of Symptomsmentioning
confidence: 99%
See 2 more Smart Citations